PENGARUH KINERJA PERUSAHAAN, IMBAL HASIL SAHAM, DAN UKURAN PERUSAHAAN TERHADAP KOMPENSASI EKSEKUTIF - Jamal, - (2019)
This research was conducted to examine the influence of firm performance, stock returns, and firm size on executive compensation. This study uses the state- owned enterprises listed in Indonesia Stock Exchange as a sample. The sampling in this study of 17 state-owned enterprise listed in Indonesia Stock Exchange 2015-2017 by purposive sampling method. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 23 and a significance level of 5 %. Testing the coefficient of determination in this study using R Square score analysis with SPSS 23 and significance level of 5 %. The results of the testing showed that: (1) Firm Performance has a significant influence on the Executive Compensation (2) Stock Returns has no significant influence on the Executive Compensation (3) Firm Size has a significant influence on the Executive Compensation (4) Firm Perfomance, Stock Returns, and Firm Size have been able to explain Excutive Compensationas about 90.8 %.